Impactos da aprendizagem da filosofia no ensino m??dio sobre a forma????o filos??fica do pedagogo: um estudo de caso na UFPA - Braga, L??lio Favacho (2017)
This thesis aims to investigate the possible impact of the learning of Philosophy in the High School of the Par?? state public school and its possible influence on the philosophical formation of Pedagogy students of the Federal University of Par?? - UFPA. The case study was used as an investigative method and, as analysis technique, the analysis of content applied to the elements collected in the interviews of the subjects interviewed. The empirical sample of the subjects was composed of five UFPA students, who reported, through a semi-structured interview, their experiences while they were high school students from schools belonging to the State Secretariat of Education of Par?? - SEDUC-PA and as students of the discipline Philosophy of Education, already in the Pedagogy Course of UFPA. In the theoretical contextualization of this study, the works of Severino stand out, without prejudice of the other theoretical categories, that are put like sustentation of all the reflective work. In addition to a list of subsidies on the subject in the chosen literature, some courses of preparation of the teaching program of Philosophy practiced in the Schools belonging to SEDUC-PA and of the discipline Philosophy of Education belonging to UFPA were presented, with a dense description of the process On the agenda and advancing subsidies to rethink the training, both in the High School of SEDUC-PA and in the Course of Pedagogy of UFPA. The present work was concluded by explaining the scope of the pedagogical intervention of Philosophy and evidencing its character of Paideia, as well as its limits and possibilities of interference in the education of education professionals.